Formability of roll-formed carbon fibre reinforced metal hybrid components and its experimental validation. Issue 1 (1st May 2022) - Hu, X; Creighton, C; Zhang, P; Müller, N; Reincke, T; Taube, R; Weiss, M
Abstract: Carbon Fibre Reinforced Metal Hybrid (CFRMH) materials that combine a sheet metal substrate with a reinforcing carbon fibre patch represent a promising solution to reduce weight while increasing the structural and crash performance of future automotive vehicles. CFRMHs cannot be formed with conventional stamping processes and at high volumes. This currently reduces their widespread application. Roll forming is increasingly used in the automobile industry for the forming of lightweight and high-strength metal structural components. The major deformation mode in roll forming is simple bending and this reduces interlaminar shear and compressive stresses that lead to fibre failure and delamination issues when stamping CFRMH sheet materials. This work analyses the potential of applying the conventional roll forming process for the manufacture of a simple top hat section shape from CFRMH sheet. For this, first, the material is produced in a hot press and then formed to shape in a laboratory roll forming facility at room temperature. Different layup sequences are tested, and component quality is analysed after roll forming by visual inspection. The results suggest that roll forming presents a promising manufacturing method for the production of automotive components from CFRMH sheets. The roll formed open shells are joined to produce crash box structure and tested in 3-point bending. The results show that depending on the fibre orientation a significant increase in weight specific strength is achieved.